The supportive effect of supplementation with α-keto acids on physical training in type 2 diabetes mellitus. Issue 7 (8th July 2015) - Liu, Y.; Spreng, T.; Lehr, M.; Yang, B.; Karau, A.; Gebhardt, H.; Steinacker, J. M.
<x xml:space="preserve">Abstract</x> The supplementation with α-keto acids provides supportive effects in type 2 diabetes patients undergoing physical training by improving training effects and prolonging benefit in glucose control.